Revisiting the Legacy of Islamic Legal Scholarship: The Influence of Sharia on Contemporary Legal Systems - Salman Faris TC (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
This paper explores the enduring legacy of Islamic legal scholarship and its profound impact on the development of legal systems, with a particular focus on Sharia. Beginning with an introduction, the study navigates through the historical roots of Islamic legal thought, unraveling its evolution in the early centuries of Islam. It examines the establishment of the four major Sunni schools of thought and the Shiite Ja'fari school, marking pivotal milestones in the codification of Islamic jurisprudence. A critical analysis of the key principles of Sharia forms a central part of the exploration. The study elucidates the dynamic nature of Sharia, which extends beyond a mere legal code to encompass a comprehensive ethical framework governing personal conduct, family matters, commerce, and criminal justice. The five maqasid al-Sharia, or objectives of Sharia, namely preservation of life, religion, intellect, progeny, and property, provide a robust ethical foundation for legal rulings. The paper also delves into the contributions of Islamic legal scholars to legal theory, emphasizing concepts such as 'ijtihad,' 'qiyas,' and 'istislah.' These principles have facilitated the adaptability of Sharia, allowing for independent reasoning and analogical deduction in response to evolving societal needs. Furthermore, the influence of Islamic legal principles on legal systems globally is examined, highlighting the integration of Sharia into the Ottoman legal system and its impact on legal traditions in the Middle East and beyond. The study concludes by exploring the contemporary relevance of Islamic legal scholarship. It reveals that Islamic legal principles continue to inform legal debates and policymaking, particularly in Muslim-majority countries striving to reconcile traditional Sharia principles with modern legal norms. The principles of fairness, justice, and equity found in Sharia have transcended borders, contributing significantly to the global discourse on human rights and legal pluralism.